Volatile Organic Compound Emission from Human Skin in Health and Disease - Anuja T. Mitra; Alexandra Razumovskaya-Hough; George B. Hanna (Current Progress in Medicine and Medical Research Vol. 2, 2023)
The aim of this chapter is to examine the utility of volatile organic compound (VOC) emissions derived from the human skin in the context of human health and disease. The analysis of volatile organic compounds (VOCs) emitted from the human body can provide personalised information about underlying metabolic pathophysiological processes entirely non- invasively. Despite the skin being the second largest contributor to the production of VOCs, it is an underexplored branch of the overall human volatolome and consequently the role of human skin to VOC production and the exact extent to which skin VOCs can be signatures of health and disease is unknown. This chapter explores the role of skin VOCs in the broader scientific and clinical context of the entire human volatolome. First, the literature landscape of the human volatolome and its clinical applications is described. The focus of this chapter then shifts to the human skin volatolome. Key methodological processes and challenges in skin VOC capture and analysis are considered. This is followed by a comprehensive summary and literature evaluation of research on skin VOCs in health and disease with a unique perspective on elucidating the biological origins of skin VOCs aiming to link the phenotype to the underlying disease process. Finally, the chapter concludes by discussing the current limitations of skin VOC research and suggests future research directions in this novel scientific field that may strengthen the clinical translational value of skin VOCs.